The impact of teleworking in psychologists during COVID-19: Burnout, depression, anxiety, and stress - Serrão, Carla; Rodrigues, Ana Rita; Teixeira, Andreia; Castro, Luísa; Duarte, Ivone (Frontiers in Public Health, 2022)
Background: The COVID-19 pandemic has forced mental health professionals to adapt quickly. The pandemic has created multiple new tasks for the psychologist. In addition to the various stressors closely linked to the COVID-19 pandemic, psychologists were forced to make their services more flexible. Teleworking was a way of continuing to work. Objective: This study aimed to identify the impact of working pattern on the levels of burnout, depression, anxiety, and stress. Methods: This was a cross-sectional study based on an online questionnaire applied to eighty-three Portuguese psychologists. Data were collected from May 9 to June 8, 2020, a period comprising the declaration of a national calamity and then state of emergency, and the subsequent ease of lockdown measures. The Copenhagen Burnout Inventory Scale and Depression Anxiety and Stress Scale were used. Univariate multiple linear regression models were estimated for each mental health outcome. Results: Significant differences were found between psychologists working in the workplace and in teleworking at the personal burnout, work-related burnout, client-related burnout, depression, and stress. In multiple linear regression, teleworking, not working, and being unmarried was significantly associated with higher levels of depression. Teleworking was significantly associated with higher stress scores and client-related and work burnout. Conclusions: This exceptional time of sudden, mandatory, and high-intensity teleworking, required rapid adaptation, giving rise to new stressors that might have been responsible for burnout levels in psychologists.